ACTS OF CORRUPTION IN STATE CONTRACTING AS A RESULT OF COVID-19: CIVIL SERVANT CRIME OR ADMINISTRATIVE OFFENCE? - Blas Torres Puraca (2020)
This article addresses possible corruption scenarios in direct hiring as a result of the covid - 19. The crimes committed in direct contracting are the crime of collusion and incompatible negotiation. In this sense, public officials could be criminally sanctioned, but they could also be administratively sanctioned, depending on the specific conduct, hence the importance of the difference between an official crime and an administrative infraction. To sustain this differentiation we have to refer to the principles of criminal law and the nature of the legal assets protected by each branch of law in question.